Female cosmetic genital surgery : concepts, classification, and techniques - Hamori, Christine A.; Banwell, P. (Paul E.); Alinsod, Red (New York : Thieme, 2017)
Female genital rejuvenation is a hot topic, and the procedures are growing in popularity, thanks to more media awareness of this type of surgery. This comprehensive and highly visual text covers the important issues of patient selection and patient consultation as well as fully covering all the different operative techniques along with accompanying surgical video. There is a special focus on dealing with complications and how to deal with secondary cases.
Anatomy and classification of the female genitalia : implications for surgical management / Paul E. Banwell -- Psychosocial issues and social mores in female genital aesthetic surgery : what is normal? / Kharen Ichino, Jennifer L. Walden -- Informed consent and liability in cosmetic genital surgery / Neal R. Reisman -- Labial reduction : surgical wedge technique / Christine Hamori -- Labia minora reduction surgery : curved linear resection / Red Alinsod -- Labia majora reduction surgery : majoraplasty / Red Alinsod -- Clitoral hood reduction techniques / Otto J. Placik -- Augmentation of the labia majora with fat grafting / Lina Triana, Mildred M. Martínez, Paul E. Banwell -- Augmentation of the labia majora with fillers / Nicolas Berreni -- Complications of female cosmetic genital surgery / Christine Hamori -- Perineoplasty and vaginoplasty / Marco Pelosi II, Marco Pelosi III -- Hymenoplasty / Otto J. Placik -- Auxiliary procedures / Clara Santos, Red Alinsod -- Future avenues and advances / Colin C.M. Moore -- O-shot / Charles Runels -- Transcutaneous temperature-controlled radiofrequency for vulvovaginal rejuvenation / Red Alinsod -- Fractional erbium laser for vaginal rejuvenation / Evgenii Leshunov.
Includes bibliographical references.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Master record variable field(s) change: 650
Keywords: Generative organs -- Surgery; Generative organs, Female -- Surgery; MEDICAL / Gynecology & Obstetrics; Generative organs, Female -- Surgery; Generative organs -- Surgery; Gynecologic Surgical Procedures -- methods; Genitalia, Female -- surgery; Reconstructive Surgical Procedures -- psychology; Electronic books; Electronic books